2020
DOI: 10.20944/preprints202010.0286.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human-Like Arm Motion Generation: A Review

Abstract: In the last decade, the objectives outlined by the needs of personal robotics have led to the rise of new biologically-inspired techniques for arm motion planning. This paper presents a literature review of the most recent research on the generation of human-like arm movements in humanoid and manipulation robotic systems. Search methods and inclusion criteria are described. The studies are analysed taking into consideration the sources of publication, the experimental settings, the type of movements, the techn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Additionally, we included other trajectory characteristics such as duration, distance traveled, the sum of acceleration-change (AC) and speed-change (SC). These characteristics were investigated in both jointsspace (denoted as joint-space or JS) and end-effector (denoted as EF) space (Gulletta et al, 2020); which applied to trajectory characteristics such as distance traveled, a sum of SC, a sum of AC, and the sum of JC. In total, there were 11 trajectory characteristics considered in this study:…”
Section: Methodology Experimental Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we included other trajectory characteristics such as duration, distance traveled, the sum of acceleration-change (AC) and speed-change (SC). These characteristics were investigated in both jointsspace (denoted as joint-space or JS) and end-effector (denoted as EF) space (Gulletta et al, 2020); which applied to trajectory characteristics such as distance traveled, a sum of SC, a sum of AC, and the sum of JC. In total, there were 11 trajectory characteristics considered in this study:…”
Section: Methodology Experimental Taskmentioning
confidence: 99%
“…Wurhofer et al (2015) found that a lack of transparency had a negative impact on the acceptance of robotic technology in the workplace. To address this issue, the robotics research community proposed to improve human's prediction of a robot's intention by adjusting the robot's behavior (Gulletta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angular position along the elliptical path was defined using the eccentric anomaly 1 , E, such that E = atan(ay/bx), where a and b were half the length of the major and minor axes of the ellipse, respectively. x and y were the magnitudes of the position vector in the direction of the major and minor axes in Cartesian space, respectively.…”
Section: Dependent Measures and Data Processingmentioning
confidence: 99%